Effects of yeast peptides on the growth, antioxidant and anti-inflammatory capacities, immune function, and diarrhea status of suckling calves - Liu, Xuexian; Yang, Jiashu; Yan, Yibo; Wang, Kai; Guo, Chunyan (Frontiers in Veterinary Science, 2024)
Yeast peptides, which are small-molecule active peptides extracted from yeast proteins, are known for their antibacterial, antioxidant, and anti-inflammatory properties. However, the effects of yeast peptide on suckling calves remain unclear. In this study, the effects of yeast peptide supplementation on the growth, diarrhea incidence, and immune function of calves during the suckling period were determined. Thirty newborn calves were randomly divided into two groups: the control group (CON) and the treatment group (AP), which received fresh pasteurized milk supplemented with yeast peptides (5 g/day). The experiment lasted for 49 days (7–56 days of age). The dry matter intake, body weight, diarrhea status, immune function, antioxidant capacity, and anti-inflammatory activity of the calves were analyzed. The AP group had higher dry matter intake, daily weight gain, and feed efficiency than the CON group (P < 0.05). Moreover, the duration and frequency of diarrhea were significantly lower in the AP group than in the CON group (P < 0.05). Furthermore, the immune, antioxidant, and anti-inflammatory capabilities of the AP group were significantly higher than those of the CON group (P < 0.05). These findings provide valuable insights for the improvement of early health management during calf rearing.